Ethnicity: Malay students on an American campus - Abdullah Taib (Universiti Kebangsaan Malaysia, 1979)
This case study attempts to understand patterns of social interaction of Malay students who are studying in an American campus. It was observed that Malay students have close relationship with students of their own ethnic group. They share apartments among themselves in areas which are heavily populated by other Malay students. They go out together for coffee break, shopping, play games and travel together. In contrast, they have little interaction with American students. In this study, the existence of such patterns of social interaction is explained in terms of Malay students' high feeling of ethnicity, which in turn can be understood by looking at their backgrounds in their home countries.